In situ observation of thermal-driven degradation and safety concerns of lithiated graphite anode - Xiang Liu (Nature Portfolio, 2021)
The role of the lithiated graphite anode in battery thermal runaway failure remains under intense investigation. In this work, with multiple in situ synchrotron X-ray characterizations, the phase evolution, gas release, and lithium leaching of lithiated graphite anode are illustrated in detail.